Novel Lyssavirus in Natterer’s Bat, Germany - Freuling, Conrad M.; Beer, Martin; Conraths, Franz J.; Finke, Stefan; Hoffmann, Bernd; Keller, Barbara; Kliemt, Jeannette; Mettenleiter, Thomas C.; Mühlbach, Elke; Teifke, Jens P.; Wohlsein, Peter; Müller, Thomas
A virus isolated from a Natterer's bat (Myotis nattererii) in Germany was differentiated from other lyssaviruses on the basis of the reaction pattern of a panel of monoclonal antibodies. Phylogenetic analysis supported the assumption that the isolated virus, Bokeloh bat lyssavirus, may represent a new member of the genus Lyssavirus.